The Mobile Broadband and Fixed Broadband Battle in Swedish market: Exploring complementary or substitution - Chalita Srinuan; Pratompong Srinuan; Erik Bohlin (International Telecommunications Society (ITS), 2010)
The mobile broadband (MBB) in Swedish market has become a more attractive opportunity for service providers, with growing demand for ubiquitous broadband connectivity after the mobile operators got 3G license in 2000. MBB seems to have more advantage compare to Fixed broadband (FBB) in term of mobility, compatibility and quality of service. This paper aims to explore the current broadband situation in Swedish market, in particular whether the mobile broadband is a complementary or substitute by using descriptive analysis. The data is collected from the Post- och telestyrelsen (PTS) Survey and the secondary data from PTS during 2002-2009. The findings indicate that the MBB and FBB subscribers remain growing, but the issue of complementary and substitution between MBB and FBB cannot be given an answer at this stage. The crucial problem of comparing MBB and FBB is the different units of measurement. Also, the potential of avoiding regulation by service providers is discussed since the market participants in FBB and MBB services are the same players. The rapid growth of MBB together with a lower degree of regulation in mobile services may attract the market player to put their effort more in MBB market. Moreover, the gap between broadband infrastructure coverage and the usage of this service is huge. Thus, the inefficiency of BB infrastructure utilization becomes another issue that NRAs could consider.
Keywords: D22; L11; L52; L96; 330; Mobile broadband; Fixed broadband; Complementary; Substitution